First report of refractory grey zone lymphoma in an adolescent patient treated successfully with pembrolizumab - Dudzik, Maria; Zaniewska Tekieli, Anna; Balwierz, Walentyna; Skoczeń, Szymon; Goździk, Jolanta; Czogala, Malgorzata (Contemporary Oncology/Współczesna Onkologia, 2025)
Grey zone lymphoma (GZL) is a rare and aggressive B-cell lymphoma, exhibiting features of both diffuse large B-cell lymphoma and classical Hodgkin’s lymphoma (cHL). Due to its rarity, especially in paediatric patients, no standardized treatment protocols exist. The disease presents diagnostic challenges and limited treatment options. Recent studies suggest that immune checkpoint inhibitors, such as pembrolizumab, may offer a promising treatment for refractory cases. A 15.5-year-old male initially presented with huge mediastinal tumour, fluid in the pleural cavity, enlargement of supraclavicular lymph nodes, left subclavian and diaphragmatic nodes and lung infiltration. Initial histopathological examination suggested cHL, but after progression on the first-line therapy (EuroNet-PHL-C2 protocol), biopsy confirmed mediastinal GZL. Despite further chemotherapy (COP, R-COPADM, R-CYM, R-CYVE, R-ICE), the disease continued to progress. Pembrolizumab was introduced after further progression. Following eight months of the treatment, positron emission tomography scans showed a complete metabolic response. The patient underwent autologous stem cell transplantation and continued pembrolizumab for 27 months, maintaining stable small residual tumour with a complete metabolic response. This case highlights the diagnostic challenges and treatment difficulties in paediatric GZL. Pembrolizumab, a programmed death 1 inhibitor, demonstrated efficacy in a heavily pretreated patient with refractory disease. Although pembrolizumab is widely used in adults, this successful application in paediatric GZL suggests its potential as a therapeutic option for this rare lymphoma subtype also in children and adolescents. Pembrolizumab occurred to be effective in refractory paediatric GZL, supporting the need for further studies to assess its safety and efficacy in larger cohorts.